Problematyka etyczna w pierwszych dziełach o rachunkowości - Garstka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2015)
Accountants recently had the opportunity to celebrate 20 years of existence in Polandthe regulating of accounting. The act was adopted by parliament in 1994. 500years before the treaty about double accounting was reprinted by Pacioli. The editionof Tractatus XI. Particularis de computis et scripturis was an (epic) epoch-makingevent designating the beginning of a new field of economic sciences. The ideaof the double accounting was known before, not only because of Pacioli, but alsothrough Cotruglio, who described it 36 years earlier.Recently in accounting, as well as in the broadly understood economy, thereis a particular emphasis put on ethics, moral values and professional attitudes. It isworth considering whether and on what scale they were present in the early worksof Accountancy 550 years ago, how their representatives approached the subjectsthe beginning of a written history of accounting.The article presents the main ideas included in the guidelines Pacioli and Cotruglioregarding double accounting, and identifies if ethical guidelines were presentsamong others guidelines. It turns out that the author of the essential work inthe history of accounting, as well as its predecessor, devoted much attention to themoral attitude of the merchant, his appropriate behavior, attitude towards customersand other people, with whom he has a business relationship.